Actividades recreativas en la escuela Isidro Ayora - Izurieta Checa, Diego Fernando (2016)
The present research the investigation is to contribute to the strengthening of academic processes performed by teachers, student’s recreational activities. Through the observing at the school where they could detect the problem, as researchers visualized in the classroom in the process of teaching and learning, there is a lack of recreational leisure activities that are aimed at recreation education, taking note that students have to coupled a new form of more formative study and the lack of recreational activities has consequences for students one of them is the low yield. The project arises from the need to investigate the benefits have recreational activities that will help students develop the abilities with criterion of performance, with the end to have a variety of classroom activities in the work of teachers, allowing to have a change behavior and raise the academic level of students, with this is to have an inclusive education and all students improve their interpersonal relationships. The methodology applied in this work is the descriptive method, where the population was the object of study were students, surveys were conducted, the results were tabulated and could determine how is the reality of the development of academic work using recreational activities in the teaching-learning process. This way you can set that this proposed work will provide a valuable contribution to education, where students are motivated, to get interested in improving in all aspects in the process of comprehensive training, plus the project developed in full will guide teachers to be used as inclusive strategies to strengthen academic processes developed in the classroom.